Investigating the interaction between spoilage bacterial growth and beef steak color stability of beef longissimus lumborum and psoas major steaks in aerobic retail display using a multi-omic approach - Smith, Colton L., author; Nair, Mahesh N. , advisor; Geornaras, Gina, committee member; Delmore, Robert J., committee member; Metcalf, Jessica L., committee member; Prenni, Jessica E., committee member (Colorado State University. Libraries, 2025)
One of the primary drivers of fresh red meat wastage is discoloration at the retail and consumer levels of distribution. Although discoloration is not necessarily an indicator of meat freshness, discolored meat is often reduced in price or discarded as it is viewed by consumers as spoiled. In other words, a meat product is spoiled once it is no longer desirable to the consumer. Research evaluating meat spoilage dates back nearly a century and these studies have yielded tremendous improvements to extending meat shelf-life, especially from a microbial and meat color standpoint. The intrinsic and extrinsic factors contributing to muscle-specific discoloration in beef have been investigated extensively. However, the impact of microbial growth on meat discoloration remains unclear. Previous studies have indicated that the growth of spoilage bacteria during retail display decreases the color stability of aerobically packaged beef. Therefore, the objective of Chapter 2 was to investigate the impact of the growth of common meat spoilage bacteria on the color stability of color-stable (longissimus lumborum; LL) and color-labile (psoas major; PM) beef muscles. Beef striploins (LL) and tenderloins (PM) (USDA Choice, n = 8) were wet aged (14 d), after which they were decontaminated and fabricated into 1.27-cm thick steaks. Steaks were randomly assigned as decontaminated (DCON) or inoculated (INOC). The surface of INOC steaks was inoculated (ca. 4 log CFU/cm2) with a mixture of five spoilage bacteria, while an equivalent volume of phosphate-buffered saline was applied to the surface of DCON steaks. Steaks were aerobically retail displayed for up to 9 d. Each day, objective and subjective color evaluation and microbiological analyses were conducted. Aerobic plate counts on INOC steaks were 8.9 (LL) and 9.3 (PM) log CFU/cm2 at the end of retail display. Corresponding counts on DCON steaks were <2.7 (LL) and <3.4 (PM) log CFU/cm2. For LL steaks, there was a treatment by display day interaction (P < 0.05) for lightness (L*), redness (a*), yellowness (b*), lean color scores, surface discoloration, and bacterial levels. On days 6–8, redness was lower (P < 0.05) for INOC compared to DCON LL steaks, while lean color scores and surface discoloration were lower (P < 0.05) for DCON compared to INOC LL steaks. For PM, there was a treatment by display day interaction (P < 0.05) for a* values, surface discoloration, and bacterial levels. Surface discoloration was greater (P < 0.05) for INOC steaks compared with DCON steaks on days 4 and 5. The results indicate a connection between surface discoloration and microbial growth on beef LL and PM steaks, and differences in bacterial growth kinetics could explain some of the differential color stabilities between these muscles. Based on the data obtained in Chapter 2 and the lack of previous studies that have evaluated bacterial function during meat spoilage, the objective of Chapter 3 was to explore the functional role of spoilage bacteria on fresh beef LL steak discoloration during retail display using a multi-omic approach. Beef LL were wet-aged, decontaminated, and cut into steaks. Half of the steaks were then assigned as inoculated (INOC; inoculated with a mixture of spoilage bacteria), and the other half remained uninoculated DCON). The aerobically packaged steaks were placed into a retail display and analyzed daily for objective and subjective color, microbial load, lipid oxidation (TBARS), pH, 16S rRNA gene sequencing, metatranscriptomics, and surface metabolomics. The a* (redness) and b* (yellowness) values of the treatments were similar (P  0.05) from days 0-4 but were lower (P < 0.05) in INOC compared to DCON on days 5-7. The INOC had a higher (P < 0.05) microbial population throughout the display period. The metabolomic analysis indicated that there were 10 metabolites that had treatment-by-day interactions (P < 0.05). Results from 16S rRNA gene sequencing of INOC samples indicated beta diversity was influenced (P < 0.05) by display day. Metatranscriptomics revealed 785 transcript changes (P < 0.05) between days 3 and 6. In general, glucose mediated carbohydrate metabolism associated gene transcripts did not change throughout the display period. However, there was a steady increase in alternative pathways of generating citrate cycle intermediates, derived from amino and fatty acids. Results from this study indicated that spoilage bacteria can influence color stability, and changes occurring in microbial metabolism align with changes in the steak discoloration. Further research is needed to investigate pathway intermediates and metabolites to better elucidate the microbial function in discoloration in aerobically packaged fresh beef LL steaks. Similar to Chapter 3, an identical experiment was conducted with color labile beef PM to determine bacterial function on color labile muscles. The objective of Chapter 4 was to characterize the bacterial functional changes during the discoloration of beef PM steaks. Ten beef PM muscles (n = 10) were aged for 14 days, decontaminated, and fabricated into steaks. Steaks from each PM were divided into treatments: decontaminated (DCON) and inoculated (INOC; with six spoilage bacteria). They were then aerobically packaged and placed in a retail display case for 7 days. Each day, one steak per treatment per replicate per trial was sampled for instrumental and visual color analysis, microbial enumeration, lipid oxidation, pH, 16S rRNA gene sequencing, surface metabolomics, and metatranscriptomics. There was a treatment by display day interaction for (P < 0.05) a* values and percentage discoloration, with DCON remaining redder with less discoloration compared to INOC until day 3 Metabolomic analysis showed a treatment by display day interaction (P < 0.05) for glucose, galactose, phenylalanine, and tyrosine. The metatranscriptomic data analysis revealed 32 Kyoto Encyclopedia of Genes and Genomes Orthologs (KO) with changes (P < 0.05) from bacteria on PM INOC steaks. The KO abundance changes were between days 2 and 3 and days 3 and 4 of display. The most pronounced changes in KO between days 3 and 4 (30 changes) coincided with the largest decreases in a* values and increases in percentage discoloration for INOC steaks. The results suggest that bacteria on PM steaks may be decreasing reliance on glucose metabolism early in the display period and simultaneously increasing usage of aromatic amino acids. These changes in bacterial metabolism might be contributing to the relatively quick discoloration in PM, along with other muscle-specific factors.